From phenols to quinones: Thermodynamics of radical scavenging activity of para-substituted phenols. (October 2019) - Michalík, Martin; Poliak, Peter; Lukeš, Vladimír; Klein, Erik
Abstract: Radical scavenging activity and subsequent oxidation resulting in quinone products represent one of the important features of phenols occurring in plants and other biological systems. However, corresponding thermochemistry data can be still considered scarce. For phenol and 25 para -substituted phenols, we investigate the thermodynamics of the individual reaction steps, including three subsequent hydrogen atom transfers, as well as hydroxyl HO radical addition, leading to final ortho -quinone formation. The substituent and solvent effect of water on corresponding reactions enthalpies is elucidated. Solvent enhances substituent induced changes in the investigated reaction enthalpies. The reliability of employed computational methods for the thermodynamics of hydrogen atom donating ability of studied phenols and catechols is assessed, too. Obtained linear equations enable estimation of studied reaction enthalpies from Hammett constants of substituents. Graphical abstract: Image 1 Highlights: Radical scavenging activity and oxidation of phenols is studied. Studied reaction steps include three hydrogen atom transfers and HO. addition. Thermochemistry of individual processes is investigated using DFT methods. Found results allow water solvent effect analysis and substituent effect prediction. Performed calculations provide reliable phenolic O–H bond dissociation enthalpies.